Development of exposure assessment method with the chamber. (May 2015) - Kato, N; Koyama, Y; Yokoyama, H; Matsui, Y; Yoneda, M
Abstract: This study aims at developing the measurement method of nanoparticle concentration and at getting a representative value of nanoparticle uniform concentration due to chamber ventilation. We conducted a chamber equipped with HEPA filter and control the background nanoparticles concentration by using an adequate ventilation. Then, we used generator to evaluate concentration in the chamber uniformity. We measured background value and source counts at the particle size distribution by SMPS. In addition, we performed numerical analysis with CFD model OpenFoam. As results, we found that there is no aggregate in experimental conditions in this study. Though we confirmed that it is difficult to uniformalise nanoparticle concentration, However we also found simulation results showed higher reproducibility. Therefore, we could assess nanoparticle size distribution and concentration in our chamber at this stage.